Perspectives on occupational therapy transformation in South Africa - Duncan, E M (Division of Occupational Therapy, 2017)
This minor dissertation is built around the Vona du Toit Memorial lecture that was given, by the author, to the Occupational Therapy Association of South Africa (OT ASA) in July 1999. The central theme of both the lecture and the dissertation is professional transformation. the impetus for which is seen to reside in the axiology of the profession, starting with the morn! values, attitudes and beliefs of individual practitioners and moving towards a collectively revisioned professional ontology. It is proposed that the ·identification, analysis and resuscitation of the profession's ethos at an individual level will ultimately impact transformatively on the nature and characteristics of the profession collectively. Particular emphasis is placed on undergraduate ethics curriculum reform for the vision of transform3tion at an individual level to be realised. The dissertation documents the pilot phase of a dialectical research cycle (Reason 1981) during which the author developed perspectives about the ethical concerns that the occupational therapy profession in South Africa needs to consider in the light of its past during apartheid and in view of its future in a developing nation. It contains a conceptual analysis of the pivotal role that professional ethics and morality will have to play in effecting fundamental change in the philosophical, structural, political and education at dimensions of the profession in response to the unique demands of the African context and suggests practical educational strategies through which attitudinal transformation in undergraduate occupational therapy students may be achieved.